Fenomena Rush terhadap Perbankan pada Masa Krisis Moneter di Indonesia, 1997-1998 - Siti Solihah; Djono Djono (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aims to determine the background of the rush, the process of the rush phenomenon, and the Indonesian government's policy regarding the rush in 1997-1998. The research method used is the historical method with four stages: heuristics, source criticism, interpretation, and historiography. This study uses primary sources in the form of newspaper archives such as Analisa, Bali Post, Berita Yudha and official documents as well as secondary sources in the form of journals, books, and research reports. Data collection techniques used are document study and literature study. The data analysis technique used is historical analysis with a socio-economic approach. The results of the study indicate that Indonesia's foreign debt, especially the private sector, which continues to swell and is exacerbated by the contagion of the Baht crisis in Thailand, is the cause of the rush. News about the maturity of Indonesia's private debt in 1998 caused public panic. Seeing the continuing turbulent situation of the Indonesian economy, the government then requested assistance from the IMF. One of the IMF programs was the closure of 16 banks, but this policy actually resulted in a decline in public confidence in banking, resulting in massive withdrawals of funds from banks that were not liquidated, such as Bank Danamon, BCA, Bank Bali, and Bank Lippo. The government's policy to overcome the rush is to tighten liquidity by raising interest rates, providing Bank Indonesia Liquidity Assistance (BLBI), and providing guarantees to customers, also known as Blanket Guarantees.